Implementasi Jenjang Karir Perawat Klinik terhadap Kepuasan Pasien: studi rumah sakit Pertamina Cirebon - Nevi Kuspiana Lesmana; Asep Setiawan; Murtiningsih (Health Information : Jurnal Penelitian, 2020)
The nurse career level started since the regulation governing nurse career system in Indonesia. This research aims to determine the influence of individual factors of the patient and the implementation of the nursing clinic career path to satisfaction in hospital Pertamina Cirebon. Design of cross-sectional research with correlational type. The sample number is 96 respondents as an inpatient. Collection of research data using the Intrument questionnaire and interviews. Data analysis using Spearman's and T-Independent trials. The results proved that the implementation of the nurse's career level has an influence on the dimensions of patient satisfaction with P value 0.000. Therefore it is recommended to hospital management in applying the career path of clinic nurses need to be a commitment to leadership, cost allocation, adequate nursing resources, improving the welfare of nurses and completing the facilities.